Familiarity in the Context of Risk Assessment of Transgenic Crops: Focus on Some Countries in the Americas - Capalbo, Deise M. F.; Macdonald, Phil; Fernandes, Patricia Machado Bueno; Rubinstein, Clara; Vicién, Carmen (Frontiers in Bioengineering and Biotechnology, 2020)
Problem Formulation is the formal opening stage of a risk assessment that determines its purpose and scope and so guides the gathering of information data. The concepts of Familiarity and History of Safe Use are an integral part of Problem Formulation. These concepts do not replace the case-by-case approach and are not taken as safety standards but are valuable components of the process that shape the generation of plausible, testable risk hypotheses. The International Life Sciences Institutes in Brazil and Argentina have facilitated numerous discussions on the scientific principles for risk assessment of transgenic crops in the Latin American region in the past 5-6 years. The session held at ISBR 15th elaborated on the familiarity concept and derived tools and their role in the evolution of risk evaluation criteria. Examples of how different countries in the Americas interpret and apply these conceptual tools show that familiarity is a valuable concept, although terms are very often confused and vaguely defined. Formalizing these terms with clear definitions and scope of application in guidelines and regulatory documents would reduce ambiguity, enhance predictability and add transparency to the evaluation processes.